DMP model - Pantelić Svetlana (Bankarstvo, 2014)
In 2010 the Nobel Prize in Economic Sciences was awarded to Dale Mortensen, born in 1939 in Oregon, USA. He majored in economics and mathematics, and defended his doctoral dissertation at Northwestern University. He was a researcher and professor for full 47 years, having authored numerous papers, either by himself or in cooperation with other scientists. In addition to Mortensen, the 2010 Nobel Prize was also awarded to Peter Diamond and Christopher Pissarides for their contribution to the analysis of markets with search frictions, especially when it comes to employment. They created the DMP model, named after the first letters of their last names. Today this is an analytical instrument most used for analyzing unemployment, formation of wages and job vacancies. This model can be used to assess the impact of various factors of the labor market on unemployment, wages and job vacancies. The concerned Nobel Prize winners formulated the theoretical framework for markets with search friction. Diamond performed the analysis of such markets' foundations; Mortensen and Pissarides expanded this theory and applied it on the labor market. The model designed by these laureates helps us realize how regulations and economic policy affect unemployment, job vacancies and wages. This may refer to the amount of unemployment benefits, or certain regulations in respect of hiring and dismissing people. One of the conclusions is that more generous benefits for unemployed people result in higher unemployment rates and longer job search. In addition to the labor market, the search friction theory may be applied in many other fields, especially at the real estate market.